Expression of p16 in sporadic primary uveal melanoma - Kaczmarek, A.; Mackiewicz, A.; Romanowska, B.; Kwiatkowska, E.; Heitzman, J.; Stachura, J.; Lamperska, K.; Mackiewicz, K.; Starzycka, M. (Contemporary Oncology/Współczesna Onkologia, 1999)
In 41 cases of sporadic primary uveal melanoma expression of p16, mutations in coding region and methylation of CpG islands in promotor region were studied. Expression of p16 was studied by immunohistochemistry and recorded by assessment of proportion of positive tumor cells and staining intensity. Results were expressed as staining index (IRS). Point mutations and mrthylation of CpG islands in promotor region of this gene were analyzed by PCR-SSCP method and PCR combined with chemical modification of studied DNA. In 15% of cases less than 10% of melanoma cells were p16 positive, in 70% of cases less than 50% of cells, while in 7% more than 80% of cells stained for p16 (mean IRS for all cases was 4.87-2.73). Analysis of intragenic mutations revealed in two patients substitution in codon 84 GAC/GAT – silent mutation. No methylation in CpG island in promotor region of p16 was found.